(untitled) (Kronika Bydgoska, 2012)
The author published a description of the condition of the mint buildings in Bydgoszcz, dating back to the year 1745, prepared due to the proceeding ownership disputes over land. The description is focused on the ruined mint buildings, looted eąuipment of the plant and tools. It shows a picture of its progressing devastation, due to which the mint was finally closed down in 1765.